Answer: x=−2 and y=−5
Step-by-step explanation: 2x−y=1;12x−5y=1
Multiply the first equation by -6,and multiply the second equation by 1.
−6(2x−y=1)
1(12x−5y=1)
Becomes:
−12x+6y=−6
12x−5y=1
Add these equations to eliminate x:
y=−5
Then solvey=−5for y:
y=−5
Now that we've found y let's plug it back in to solve for x.
Write down an original equation:
2x−y=1
Substitute−5foryin2x−y=1:
2x−(−5)=1
2x+5=1(Simplify both sides of the equation)
2x+5+−5=1+−5(Add -5 to both sides)
2x=−4
2x
2
=
−4
2
(Divide both sides by 2)
x=−2